2021
DOI: 10.1155/2021/1498924
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Upregulation of MRPL13 as a Novel Prognostic Marker Associated with Overall Survival Time and Immunotherapy Response in Breast Cancer

Abstract: Mitochondrial ribosomal protein (MRPL) genes have been reported to participate in many cellular processes, such as cell proliferation, apoptosis, and cell cycle. Meanwhile, the occurrence rate of breast cancer (BRCA) in China steadily increased. Exploring the prognostic value of MRPL genes in BRCA could provide novel biomarkers for BRCA. In this study, to identify prognosis-related genes in breast cancer, the P value and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 43 publications
(59 reference statements)
0
7
0
Order By: Relevance
“…Another study reported that high MRPL13 is a poor prognostic factor for BC, and it can be used as a molecular marker for prognosis judgment and as a potential therapeutic target [24,44]. It is worth noting that MRGs are associated with the immune response and cell death [45,46], which also proves the reliability and potential to be used as biomarkers of our risk signature.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Another study reported that high MRPL13 is a poor prognostic factor for BC, and it can be used as a molecular marker for prognosis judgment and as a potential therapeutic target [24,44]. It is worth noting that MRGs are associated with the immune response and cell death [45,46], which also proves the reliability and potential to be used as biomarkers of our risk signature.…”
Section: Discussionmentioning
confidence: 83%
“…[60, 61], MTFHD2 [62], MRPL13 [24,44,45], TP53AIP1 [43] and BCL2A1 [63]), the function of other genes and the underlying mechanism of these 8 MRGs need to be further investigated, and we will conduct corresponding experimental studies in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Xin Feng et al identified a gene signature that includes the J chain gene able to discriminate head and neck squamous cell carcinoma patients with better overall survival probability [ 68 ]. Moreover, recent studies revealed that a high J chain expression is associated with better prognosis in sarcoma [ 69 ] and breast cancer patients [ 70 , 71 ]. These data validate our hypothesis that the higher expression of J chain might reflect the activation of a local humoral immunity able to control tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial ribosomal proteins (MRPs) are important components of mitochondrial translation mechanisms. It has been found that MRPs are highly invasive and metastatic to breast cancer [4][5], colorectal cancer [6] and ovarian cancer [7]. The location of enhanced expression can predict the location of tumor occurrence, which indicates that MRPs are closely related to the occurrence and development of tumors.…”
Section: Introductionmentioning
confidence: 99%